Analysis Implementation of The TPACK Approach by High School Chemistry Teachers - Dewi Handayani; Alexon Alexon (Gawi: Journal of Action Research, 2025)
The aim of this research is to study the TPACK skills of chemistry teachers at state high schools in Bengkulu City. The questionnaire results showed that all aspects of TPACK were in the excellent category (mean 85.96%). However, the results of the observations were lower than expected overall, particularly for TK, TCK, and TPACK aspects, which were still considered fair to good. This signals a disconnect between teacher beliefs and the in-class execution. Supporting factors for TPACK implementation include school support, facilities, and teacher motivation, while hindering factors include limited student device ownership, limited internet connectivity, and limited learning time. Therefore, the application of TPACK by chemistry teachers is well implemented but could be further improved by creating technology that is more consistent across learning activities.